2010
DOI: 10.1017/s0001924000003730
|View full text |Cite
|
Sign up to set email alerts
|

Design and realisation of a two-seater aircraft powered by fuel cell electric propulsion

Abstract: The main objective of the project is to develop and validate the use of a fuel cell based power system for the propulsion of more/all electric aircraft. The Rapid 200-FC two-seater electric-motor-driven aeroplane which is powered by fuel cells is at present being completed and will be validated during a flight test in Autumn 2009. Several configurations have been evaluated in order to install the new energy and propulsion system on board while maintaining the centre of gravity within allowable limits. The fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Electric propulsion is a popular system for small and micro RPAS [5,6]. Electric propulsion is known to have a favorable electrical and mechanical efficiency while being reliable due to the simple mechanics and reduced moving parts compared to IC engines [7][8][9][10]. These systems are further divided into active and passive systems, which depend on the type of bus connection between the electric machine and the battery [9].…”
Section: Battery Poweredmentioning
confidence: 99%
“…Electric propulsion is a popular system for small and micro RPAS [5,6]. Electric propulsion is known to have a favorable electrical and mechanical efficiency while being reliable due to the simple mechanics and reduced moving parts compared to IC engines [7][8][9][10]. These systems are further divided into active and passive systems, which depend on the type of bus connection between the electric machine and the battery [9].…”
Section: Battery Poweredmentioning
confidence: 99%
“…The fuel cell was the primary power source with the battery assisting during takeoff and climb [1,3]. Romeo and Borello [4] presented a preliminary design of the general aircraft propulsion system for Rapid 200-FC two-seater aircraft. The propulsion system consists of brushless electric motors, inverter, converter, fuel cell and battery.…”
Section: Introductionmentioning
confidence: 99%
“…The high efficiency, two-seater aircraft Rapid200, manufactured by Jihlavan Aircraft (now Sky Leader), was selected for conversion from over more than one hundred light sport aircraft through a multi-criteria analysis performed by the Politecnico di Torino. After the selection of the aircraft for conversion [1] an extensive conversion design activity was undertaken. The first step was to define the demonstrative mission; a complete, but limited, mission profile was selected by the consortium since the demonstration goal was to show the feasibility of a new concept propulsion system.…”
Section: General Introductionmentioning
confidence: 99%
“…The first step was to define the demonstrative mission; a complete, but limited, mission profile was selected by the consortium since the demonstration goal was to show the feasibility of a new concept propulsion system. The requested mission performances were based on a parametric study and system architecture design which was conducted by the authors and is reported in [1]; mission properties were chosen because they could guarantee that the mission could be flown while keeping the total weight at around 550 kg, i.e. the maximum total weight at which original RAPID200 was tested.…”
Section: General Introductionmentioning
confidence: 99%